Correlation between carrier and space vector based random PWM techniques for induction motor drive - Nithya Lavanya, S; Bramhananda Reddy, T; Vijay kumar, M (International Journal of Engineering and Technology, 2018)
Conventional pulse width modulation (PWM) techniques for voltage source inverter (VSI) generate high amount of harmonics at and around harmonics of switching frequencies. These causes acoustic noise and electron magnetic interference to the nearby electronic systems. In this paper different random PWM techniques were proposed for two-level VSI. The implementations of these PWM techniques were presented based on carrier comparison approach and digital space vector approach. Moreover correlations between these two methods were also presented.Â Â